A Call for Adopting High-Dose Influenza Vaccines for Adults Aged 65 and Above in Gulf Cooperation Council (GCC) Countries - Salah T. Al Awaidy; Parvaiz A Koul; Faryal Khamis; Fatima Al Slil; Imane Jroundi; Fatima Al Olama; Khalid Hamid Elawad; Musallam Yunus Hassan Abuhasan; Fana Al Oraimi; Mine Durusu Tanriover; Hassan Zaraket (Springer, 2024)
Abstract Seasonal influenza poses significant health and economic challenges globally each year, particularly impacting the elderly population (aged ≥ 65 years) with increased rates of hospitalization, and mortality. The population of older adults is steadily increasing in the Gulf Cooperation Council (GCC) countries and is likely to increase even further. In addition, there is a high burden of chronic comorbidities in these countries like diabetes and obesity, which increases the likelihood of severe consequences of influenza infection. The GCC countries also host mass gathering events like Hajj, Umrah pilgrimage, Arba'een (nearby Iraq) pilgrimage, and international sports and business events, which further intensify the risk of outbreaks like influenza. These events facilitate the mixing of visitors from various countries. Thus, influenza activity in this North Hemisphere (NH) geography is usually present even before the availability of NH seasonal influenza vaccine. This is especially problematic for the elderly, whose protection from the previous year's immunization would have waned. Higher dosages of antigens or adjuvants have been used to improve immunogenicity in older people with superior vaccine effectiveness. Therefore, there is a compelling argument in favor of the implementation of high-dose seasonal influenza vaccines in the GCC countries to improve the protection of individuals aged 65 years and older against influenza infection and associated severe complications.